The Inhibitory Effect of GR32191, a Thromboxane Receptor Blocking Drug, on Human Platelet Aggregation, Adhesion and Secretion - Hornby, E J; Foster, M R; McCabe, P J; Stratton, L E (Thrombosis and Haemostasis, 1989)
GR32191, a potent selective thromboxane receptor antagonist, has been shown to inhibit completely prostaglandin endoperoxide and thromboxane A2 (TxA2)-induced platelet aggregation, [14C]-serotonin secretion and β-thromboglobulin secretion. Deposition of human platelets onto damaged rabbit aorta in vitro is reduced in the presence of GR32191 which appears to inhibit aggregation of platelets but not direct adhesion of platelets to subendothelium. The effects of non-prostanoid platelet activating agents whose mode of action requires the biosynthesis of TxA2 are also inhibited by GR32191. Prostanoids which inhibit platelet function, such as prostacyclin or PGD2, retain their inhibitory properties in the presence of GR32191 which does not inhibit phospholipase A2, prostaglandin cyclooxygenase, thromboxane synthase, 12-lipoxygenase or cAMP phosphodiesterase activity. The inhibitory action of GR32191 on platelet aggregation, mural thrombus formation and platelet protein storage granule secretion suggests that it has potential in treatingthrombotic disease in man.
Keywords: GR32191; Thromboxane receptor antagonist; Adhesion; Secretion; Platelet aggregation